Lessons for a future advisory center on international investment law - Robert W. Schwieder (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2018)
To level the playing-field in investment-state dispute-settlement, an advisory center on international investment law (ACIIL) should be established. But any center must be carefully constructed to maximize its impartiality, capture a broad base of political and economic support and provide high-quality services while maintaining a cost-effective structural footprint.
Keywords: 330